Lactobacillus fermentum HP3–Mediated Fermented Hericium erinaceus Juice as a Health Promoting Food Supplement to Manage Diabetes Mellitus - Chaiyavat Chaiyasut (2018)
© The Author(s) 2018. The current study investigated the antidiabetic property of Lactobacillus fermentum HP3–mediated fermented Hericium erinaceus juice (FHJ) using male Wistar rats with streptozotocin-induced diabetes mellitus (DM). FHJ was prepared using boiled mushroom juice and L. fermentum HP3. Amino acid and γ-aminobutyric acid (GABA) content of FHJ was analyzed. Streptozotocin-induced DM rats were supplemented with FHJ in a pre- and posttreatment method. The changes in plasma insulin, plasma glucose level, glycated hemoglobin (HbA1c), representative cytokines, and the antioxidant system were assessed in experimental rats using spectrophotometric methods and enzyme-linked immunosorbent assay. The supplementation of FHJ improved the body mass, insulin level, and recovery progress of hyperglycemia. HbA1c level was altered by the FHJ intervention. The inflammatory cytokines level was suppressed in FHJ supplemented group compared with control. Intervention of FHJ and insulin improved the production of interleukin-10 and transforming growth factor-–β1 in DM rat. The study suggested that fermented H erinaceus juice may be used as one of the food-based health-promoting supplement to manage DM along with medication.